(untitled) (Journal of Medical & Health Sciences Review, 2025)
Female Infertility is a well-known health problem that is very common in females. Everyone wants to have offspring but many couples fail to be parents after a year of unprotected sexual intercourse which is widely recognized as Infertility. Many factors are responsible for Female Infertility including the abnormalities of the Cervix, Ovaries, Fallopian Tubes, Uterus (polyps in the uterus), Endometriosis, Pelvic Adhesions, Irregular menstrual cycle, and syndromes like Poly Cystic Ovary Syndrome (PCOS). Some other factors that are accountable for Female Infertility are increased Age, Use of Tobacco, Use of Alcohol, and Being Overweight leading to obesity or being Underweight.Conclusion: PCOS is considered as one the major cause of Female Infertility. All the causes of Female Infertility can be managed by consulting doctors on scheduled routines and quitting bad habits of smoking, alcohol, or tobacco consumption along with keeping a healthy body weight. Conclusion: PCOS is considered as one the major cause of Female Infertility. All the causes of Female Infertility can be managed by consulting doctors on scheduled routines and quitting bad habits of smoking, alcohol, or tobacco consumption along with keeping a healthy body weight.